Saline lake development in the Aptian post-rift phase of the Tucano Basin: Tectonic and paleogeographic implications - Varejão, Filipe Giovanini [UNESP]; Warren, Lucas Veríssimo [UNESP]; Freitas, Bernardo Tavares; Neumann, Virginio Henrique; Assine, Mario Luis [UNESP] (Elsevier, 2019)
The Aptian is the age of the evaporitic transitional megasequence in the Brazilian marginal basins as well as in the interior rift basins of the northeast region. The Marizal Formation is interpreted as a fluvial system developed in the inherited rift axis of the Tucano Basin. In its middle portion, after a quick transgressive event, a mud-dominated interval took place, which is enclosed in the Amargosa Bed. This transgressive marker bed is rich in fish fossils with Tethyan affinity attesting to an estuarine environment in the southern portions of the basin. The same transgressive event occurs in the Barbalha Formation of the Araripe Basin, where a mud-dominated lacustrine system is interpreted in the Batateira Bed. While lakes developed in the Araripe Basin and a transitional marine environment is attested to the southern portions of the Tucano Basin, there is no information of how these systems were interconnected. Here we discuss sedimentologic, stratigraphic and geochemical data of the Amargosa Bed in the North Tucano Basin, correlating it with time equivalent marker beds of other locations in the Northeast Brazil. Our data show that deposition of the mixed carbonate-mud interval of the North Tucano Basin was developed in a saline lake with local evidences of seismic-induced soft-sediment deformation structures. Although climate seasonality controlled high-frequency base-level changes, our findings reveal that local fault reactivation was responsible for the space generation, triggering the lake formation in the basin depocenter. This situation is uncommon for thermal subsiding basins that lack mechanical influence and have several implications for the evolution of intracontinental rift basins of the Brazilian Cretaceous. Also, lakes from Araripe, Jatobá and North Tucano basins were probably connected by the continental paleodrainage existent in the Aptian, carrying sediments to the estuaries developed in the Central and South Tucano basins and, thus, to the developing South Atlantic Ocean.
Keywords: Amargosa bed; Aptian; Marizal formation; Saline lakes; Seismites; Syndepositional tectonism